Low Frequency (50, 100, 200 MHz) Ground Penetrating Radar Analysis of the Nipissing Beach Ridge, Huron Mountains, MI - Hilgendorf, Zach; Morrison, Sean; Adams, Hannah (My University, 2015)
Lake Superior has undergone a number of lake level phases that have resulted in the formation of beach ridges. One beach ridge that corresponds with the Nipissing phase of Lake Superior is located 0.5 km inland from the present southern Lake Superior shore within the Huron Mountains, MI. Two parallel, low frequency ground penetrating radar (GPR) transects were collected over the ridge to better understand the subsurface stratigraphy. Preliminary results indicate that lakeward dipping reflections on top of horizontal to subhorizontal reflection patterns which indicate an aggradational and progradational coastal environment.
Color poster with text, maps, images, and charts.
Keywords: Nippising Beach Ridge (Huron Mountains, MI); High-frequency GPR; Ground penetrating radar; Posters